BODILY PARTS VYING FOR POWER: HIERARCHIES AND BODIES IN EARLY CHRISTIANITY - Vorster, Fika (Scriptura, 2002)
In this essay I argue that a rhetoric of the body exposes the all-pervasiveness of the hierarchical principle as it manifested itself in the Graeco-Roman world. The parts of the ancient body were constructed with the fabrics of the social body. Implications for an engendered interpretation of Biblical writings are indicated and demonstrated via an analysis of selected passages from the Pauline letters.